PENERAPAN MODEL PEMBELAJARAN VAK (VISUAL, AUDITORY, KINESTHETIC) DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP : Penelitian Kuasi Eksperimen terhadap Siswa Kelas VIII di SMP Negeri 2 Lembang - Yantika Nawang Wulan, Novat (2016)
PENERAPAN MODEL PEMBELAJARAN VAK (VISUAL, AUDITORY, KINESTHETIC) DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP (Penelitian Kuasi Eksperimen terhadap Siswa Kelas VIII di SMP Negeri 2 Lembang); This research was motivated by the lack of students' mathematical communication skills. The purpose of this study were: (1) to determine the quality of students' communication skills improvement by applying VAK (Visual, Auditory, Kinesthetic) mathematical learning model through a contextual approach. (2) to increase the ability of mathematical communications among students who received the VAK (Visual, Auditory, Kinesthetic) mathematics learning model with contextual approach and students who followed the conventional learning, and (3) to know the students' response to the learning of VAK (Visual, Auditory, Kinesthetic) mathematics learning model through a contextual approach. The research method used is a quasi experimental method. The research design was the non-equivalent control group design. The population of the study was class VIII students at one of junior high school in West Bandung regency in 2015/2016 school year, the sampling was not random and two classes were selected to be used as an experimental class and a control class. The experimental class was given a treatment of the application of VAK (Visual, Auditory, Kinesthetic) learning model with a contextual approach, while the control group was given a treatment of the application of conventional learning. The research instruments used were test instruments of mathematical communication skills and non-test instruments of questionnaires and observation sheets. Based on the results of this study, it was concluded that: (1) the quality of students' communication skills improvement by applying VAK (Visual, Auditory, Kinesthetic) mathematical learning model through contextual approach was at medium category, (2) the improvement of the ability of mathematical communications among the students who received the VAK (Visual, Auditory, Kinesthetic) mathematics learning model with contextual approach was better than the students who followed the conventional learning (3) the students' response towards the VAK (Visual, Auditory, Kinesthetic) mathematics learning model with contextual approach was positive.